A polyphenylene sulfide fiber composite NH2-UIO66 diaphragm and preparation method thereof
By compounding NH2-UIO66 on the polyphenylene sulfide separator through a hydrothermal method, a polyphenylene sulfide fiber composite NH2-UIO66 separator is formed, which solves the problem of gas interpenetration under alkaline conditions and achieves low resistance and high hydrophilicity. The separator has high gas resistance and high gas barrier properties, which improves gas purity and reduces power consumption.
Patent Information
- Application Number
- CN202410599971.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-15
AI Technical Summary
When the existing polyphenylene sulfide separator is used under alkaline conditions, there is a problem of gas interpenetration, resulting in a decrease in gas purity and an increase in electricity consumption.
NH2-UIO66 is compounded on the PPS separator through a hydrothermal method to form a polyphenylene sulfide fiber composite NH2-UIO66 separator, which improves the hydrophilicity and gas barrier properties of the separator.
A separator with low resistance, high hydrophilicity and high gas barrier properties is achieved, which improves gas purity and reduces power consumption.
Smart Images

Figure CN118441317B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen production by electrolysis of water, and in particular to a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm and a preparation method thereof. Background Art
[0002] Polyphenylene sulfide (PPS) is a thermoplastic resin with excellent comprehensive performance. It has excellent high temperature resistance, corrosion resistance, radiation resistance, flame retardancy, balanced physical and mechanical properties, excellent dimensional stability and excellent electrical properties. It is widely used as a structural polymer material and is widely used as a special engineering plastic after filling and modification. At the same time, it can also be made into various functional films, coatings and composite materials, and has been successfully applied in the fields of water electrolysis, electronic appliances, aerospace, automobile transportation, etc.
[0003] PPS (polyphenylene sulfide) diaphragm is a diaphragm cloth made of PPS fiber through weaving, spunlace and other processes. PPS is a high-performance special engineering plastic that can maintain stable performance under alkaline solution and high temperature conditions, so it can be used to prepare alkaline hydrogen production diaphragms.
[0004] The quality of the diaphragm is directly related to the purity and power consumption of H2 and O2. In order to ensure the safe and economical operation of the polyphenylene sulfide diaphragm, it is necessary to prevent the mixing of hydrogen and oxygen on both sides of the diaphragm to ensure the purity of the gas. Therefore, most practices are to increase the density of the diaphragm and reduce the average pore size. However, this will inevitably increase the thickness of the diaphragm, affect the surface resistance, and increase the power consumption. Therefore, it is necessary to modify the PPS diaphragm. The current modification methods are:
[0005] CN115896864A discloses a hydrogen production membrane and its preparation method and application, wherein polyphenylene sulfide or polyetheretherketone is used as the supporting material of the membrane, MOF nanoparticles (Zr6O4(OH)4-trimesic acid structure or MOF-801 structure) and an enhancer are mixed evenly in a certain proportion and then applied to the membrane. This method applies inorganic matter on the surface of the membrane by a mechanical mixing method, which improves the activity of electrolytic hydrogen production, but increases the thickness of the membrane to a certain extent.
[0006] CN115084611A discloses a sulfonated polyphenylene sulfide proton exchange membrane and a preparation method thereof, wherein polyphenylene sulfide and a proton exchange resin are reacted in a polar solvent, excess solvent and impurities are removed, and a sulfide is added to continue the reaction to form a sulfonated polyphenylene sulfide proton exchange resin. The membrane prepared by this method is more suitable for conducting protons rather than hydroxide ions.
[0007] CN113862821 discloses a polyphenylene sulfide fiber fabric type alkaline water electrolysis diaphragm, which is formed by mixing polyphenylene sulfide resin and zirconium oxide nanoparticles into granules, and then spinning them after drying to form a polyphenylene sulfide diaphragm modified with zirconium oxide. The diaphragm is woven by mixing polyphenylene sulfide and zirconium oxide, but the two substances do not blend well and are prone to physical mixing to form phase separation, which will lead to poor hydrophilicity after long-term use.
[0008] CN117107297A discloses a composite diaphragm for alkaline water electrolysis hydrogen production with enhanced gas barrier properties and a preparation method thereof, wherein a binder, a porogen, and nanometer / micrometer inorganic particles are dispersed in an organic solvent to prepare a casting liquid, the casting liquid is evenly coated on both sides of a support layer, and a support network composite membrane containing a coating is obtained after a coagulation bath treatment. The composite diaphragm has good gas barrier properties and hydrophilicity. However, it is not easy to operate, the casting liquid cannot evenly penetrate into the polyphenylene sulfide fiber cloth, and the thickness of the composite diaphragm is difficult to control. Summary of the invention
[0009] The purpose of the present invention is to provide a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The present invention composites NH2-UIO66 on a PPS diaphragm by a hydrothermal method to prepare a polyphenylene sulfide diaphragm for alkaline water electrolysis with low resistance, high hydrophilicity and high gas barrier.
[0010] To achieve the above object, the present invention provides the following solutions:
[0011] One of the technical solutions of the present invention: a method for preparing a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm, comprising the following steps:
[0012] The composite solution of NH2-UIO66 is added to the polyphenylene sulfide fiber membrane after sulfonation treatment, and a hydrothermal reaction is performed (the polyphenylene sulfide membrane is modified by using alkali-resistant and hydrophilic MOFs) to obtain the polyphenylene sulfide fiber composite NH2-UIO66 membrane.
[0013] Furthermore, the sulfonation treatment specifically includes: adding the polyphenylene sulfide fiber membrane to a sulfonation reagent, heating and reacting, to obtain the polyphenylene sulfide fiber membrane after the sulfonation treatment.
[0014] Furthermore, the sulfonating agent includes concentrated sulfuric acid with a concentration of 50 to 98 wt.% or chlorosulfonic acid with a concentration of 5 to 20 wt.%.
[0015] Furthermore, the heating reaction is carried out at a temperature of 60 to 80° C. and for a time of 1 to 1.5 hours.
[0016] Furthermore, the components of the composite solution for preparing NH2-UIO66 include zirconium salt, organic ligand, solvent and acid;
[0017] The molar ratio of the zirconium salt to the organic ligand is (1-3): (1-2).
[0018] Furthermore, the zirconium salt includes ZrF4, ZrCl4 or ZrO2; the organic ligand includes diaminoterephthalic acid (NH2-BDC); the solvent includes N,N-dimethylformamide (DMF); and the acid includes acetic acid, hydrochloric acid or hydrofluoric acid (the role of the acid is to adjust the pH value of the composite solution).
[0019] Furthermore, the temperature of the hydrothermal reaction is 100-150° C., and the time is 24-48 hours.
[0020] The second technical solution of the present invention: a diaphragm of polyphenylene sulfide fiber composite NH2-UIO66 prepared by the above preparation method.
[0021] The third technical solution of the present invention: Application of the above-mentioned polyphenylene sulfide fiber composite NH2-UIO66 diaphragm in hydrogen production by water electrolysis.
[0022] The present invention discloses the following technical effects:
[0023] (1) The polyphenylene sulfide fiber composite NH2-UIO66 diaphragm of the present invention has the advantages of low resistance (helps to conduct hydroxide ions, improve electrical conductivity, and reduce surface resistance), high hydrophilicity (the smaller the surface resistance of the diaphragm, the higher the hydrophilicity), and high gas barrier properties.
[0024] (2) The preparation method of the diaphragm of the present invention is simple. It only requires placing the PPS diaphragm into the prepared NH2-UIO66 compounding agent solution and reacting it at a certain temperature for a certain time to successfully compound NH2-UIO66 on the PPS diaphragm, which is easy to achieve industrial-grade scale-up.
[0025] (3) The present invention adopts a chemical cross-linking method to graft the hydrophilic NH2-UIO66MOF (i.e., NH2-UIO66) material onto the substrate of a commercial polyphenylene sulfide diaphragm. This method can not only reduce the surface resistance and improve the hydrophilicity of the diaphragm, but also effectively prevent the penetration of gas molecules due to the three-dimensional structure of NH2-UIO66, thereby ensuring that the gases generated at the two electrodes during the electrolysis of water will not penetrate and mix with each other, thereby ensuring the purity of the gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 This is a schematic diagram of the preparation principle of the diaphragm of the polyphenylene sulfide fiber composite NH2-UIO66 of the present invention;
[0028] Figure 2 The infrared spectra of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm prepared in Example 1 of the present invention and the commercial polyphenylene sulfide original film;
[0029] Figure 3 This is a scanning electron microscope image of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm prepared in Example 1 of the present invention.
[0030] Figure 4 This is the water contact angle effect diagram of the original commercial polyphenylene sulfide film;
[0031] Figure 5 This is a water contact angle effect diagram of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm prepared in Example 1 of the present invention;
[0032] Figure 6 This is a water contact angle effect diagram of the polyphenylene sulfide fiber composite UIO66 diaphragm prepared in Comparative Example 1 of the present invention;
[0033] Figure 7 This is a water contact angle effect diagram of the diaphragm of polyphenylene sulfide fiber physically coated with NH2-UIO66 prepared in Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0039] The schematic diagram of the preparation principle of the diaphragm of the polyphenylene sulfide fiber composite NH2-UIO66 of the present invention is shown in Figure 1 .
[0040] Example 1
[0041] A method for preparing a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm:
[0042] (1) The polyphenylene sulfide fiber membrane was cut into a size of 3×3 cm and placed in deionized water for ultrasonic treatment for 5 min, and then placed in ethanol for ultrasonic treatment for 5 min. After repeating this process three times, the polyphenylene sulfide fiber membrane was placed in an oven and dried at 60°C for 12 h to obtain a pretreated membrane.
[0043] (2) The pretreated membrane was placed in a beaker containing 40 mL of 98 wt.% concentrated sulfuric acid and heated in a water bath at 60°C for 1 h to obtain a sulfonated membrane.
[0044] (3) After the sulfonated membrane is taken out, it is washed with a large amount of deionized water until the deionized water after washing is neutral, and then placed in a vacuum oven and dried at 60°C.
[0045] (4) Preparation of the composite agent: 0.167 g (1 mmol) ZrF4, 0.19 g (1 mmol) diaminoterephthalic acid (the molar ratio of ZrF4 to NH2-BDC is 1:1) and 2 mL HF were dissolved in 30 mL DMF and mixed by ultrasonication to obtain a composite agent with a pH of 1.5.
[0046] (5) The composite agent is loaded into a 50 mL polytetrafluoroethylene-lined steel autoclave, and the diaphragm dried in step (3) is placed vertically into the composite agent so that the composite agent covers the diaphragm, and then placed in a vacuum constant temperature drying oven at 120° C. and heated at a constant temperature for 36 h to obtain a composite NH2-UIO66 diaphragm.
[0047] (6) After the NH2-UIO66 composite membrane was taken out, it was washed several times with DMF and anhydrous ethanol respectively to remove the guest molecules, and then dried in a vacuum oven at 90°C for 12 h to obtain a polyphenylene sulfide fiber composite NH2-UIO66 membrane.
[0048] The infrared spectra of the polyphenylene sulfide fiber composite NH2-UIO66 membrane prepared in this example and the commercial polyphenylene sulfide original membrane are shown in Figure 2 The scanning electron microscope image of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm prepared in this embodiment is shown in Figure 3 ; Water contact angle effect diagram of commercial polyphenylene sulfide original membrane is shown in Figure 4 The water contact angle effect diagram of the polyphenylene sulfide fiber composite NH2-UIO66 membrane prepared in this embodiment is shown in Figure 5 .
[0049] Infrared 1050cm -1 The peak at is the symmetrical stretching vibration peak of -SO2N- (Xue Yujie, Wu Bixin, Yao Dongxue, et al. Preparation of high-performance polysulfonamide acid-resistant nanofiltration composite membranes [J]. Membrane Science and Technology, 2022, 42(06): 78-86. DOI: 10.16159 / j.cnki.issn1007-8924.2022.06.010.). The polyphenylene sulfide fiber composite NH2-UIO66 diaphragm prepared in this example also has a -SO2N- peak, but the peak position has shifted to 1065 cm -1 However, it can be proved that NH2-UIO66 forms -SO2N-( Figure 2 ).
[0050] NH2-UiO66 is a MOFs material with a porous octahedral structure (Zhang HZ, Sun JY, Zhang Z-L, et al. Hybridly charged NF membranes with MOF incorporated for removing low-concentration surfactants[J]. Separation and Purification Technology, 2021, 258.). Figure 3As shown, the morphology of the prepared material was characterized by scanning electron microscopy and it was found that NH2-UiO66 showed a regular octahedral morphology with a particle size range of approximately 1 to 2 μm, and it can be clearly observed that NH2-UiO66 has been successfully compounded on the polyphenylene sulfide fiber.
[0051] The water contact angle of the commercial polyphenylene sulfide original membrane is 138° ( Figure 4 ), the water contact angle of the polyphenylene sulfide fiber composite NH2-UIO66 membrane prepared in this embodiment is 33° ( Figure 5 ); The surface resistance of the commercial polyphenylene sulfide original film tested by Princeton PARSTAT 3000-DX is 1.47Ω.cm 2 The surface resistance of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm prepared in this embodiment is 0.32Ω.cm 2 ; According to the Chinese building materials industry standard JCT211-2009 diaphragm asbestos cloth standard test, the air tightness of the original commercial polyphenylene sulfide membrane is 465mm H2O, and the air tightness of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm prepared in this embodiment is 650mm H2O; the weight of the diaphragm before composite NH2-UIO66 was weighed using an electronic analytical balance and was 0.4101g, and the weight of the polyphenylene sulfide diaphragm after composite NH2-UIO66 was 0.4162g. The calculation shows that the loading amount of NH2-UIO66 on the polyphenylene sulfide diaphragm is 14.87mg / g.
[0052] Example 2
[0053] A method for preparing a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm:
[0054] (1) The polyphenylene sulfide fiber membrane was cut into a size of 3×3 cm and placed in deionized water for ultrasonic treatment for 5 min, and then placed in ethanol for ultrasonic treatment for 5 min. After repeating this process three times, the polyphenylene sulfide fiber membrane was placed in an oven and dried at 60°C for 12 h.
[0055] (2) The pretreated membrane was placed in a beaker containing 40 mL of 60 wt.% sulfuric acid and heated in a water bath at 80°C for 1.5 h to obtain a sulfonated membrane.
[0056] (3) After the sulfonated membrane is taken out, it is washed with a large amount of deionized water until the deionized water after washing is neutral, and then placed in a vacuum oven and dried at 60°C.
[0057] (4) Preparation of the composite agent: 0.23 g ZrCl4 (1 mmol), 0.09 g (0.5 mmol) diaminoterephthalic acid (the molar ratio of ZrCl4 to NH2-BDC is 2:1) and 2 mL HF solution were dissolved in 30 mL DMF and mixed by ultrasonication to obtain a composite agent with a pH of 1.65.
[0058] (5) The composite agent is loaded into a 50 mL polytetrafluoroethylene-lined steel autoclave, and the diaphragm dried in step (3) is placed vertically into the composite agent so that the composite agent covers the diaphragm, and then placed in a vacuum constant temperature drying oven at 120° C. and heated at a constant temperature for 48 h to obtain a composite NH2-UIO66 diaphragm.
[0059] (6) After the NH2-UIO66 composite membrane was taken out, it was washed several times with DMF and anhydrous ethanol respectively to remove the guest molecules, and then dried in a vacuum oven at 90°C for 12 h to obtain a polyphenylene sulfide fiber composite NH2-UIO66 membrane.
[0060] The surface resistance of the diaphragm of polyphenylene sulfide fiber composite NH2-UIO66 was tested by Princeton PARSTAT 3000-DX and was 0.34Ω.cm 2 According to the Chinese building materials industry standard JCT211-2009 Diaphragm Asbestos Cloth Standard, the air tightness of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm is 640 mm H2O. According to the method of Example 1, the weight of the diaphragm before and after the composite NH2-UIO66 is weighed using an electronic analytical balance, and the loading amount of NH2-UIO66 on the polyphenylene sulfide diaphragm is 11.64 mg / g.
[0061] Example 3
[0062] A method for preparing a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm:
[0063] (1) The polyphenylene sulfide fiber membrane was cut into a size of 3×3 cm and placed in deionized water for ultrasonic treatment for 5 min, and then placed in ethanol for ultrasonic treatment for 5 min. After repeating this process three times, the polyphenylene sulfide fiber membrane was placed in an oven and dried at 60°C for 12 h.
[0064] (2) The pretreated membrane was placed in a beaker containing 40 mL of 80 wt.% sulfuric acid and heated in a 70°C water bath for 1.5 h to obtain a sulfonated membrane.
[0065] (3) After the sulfonated membrane is taken out, it is washed with a large amount of deionized water until the deionized water after washing is neutral, and then placed in a vacuum oven and dried at 60°C.
[0066] (4) Preparation of composite agent: 0.233 g ZrCl4 (1 mmol) and 0.167 g (1 mmol) diaminoterephthalic acid (the molar ratio of ZrCl4 to NH2-BDC is 1:1) and 3 mL HCl solution were weighed and dissolved in 30 mL DMF, and ultrasonically mixed to obtain a composite agent with a pH of 1.3.
[0067] (5) The composite agent is loaded into a 50 mL polytetrafluoroethylene-lined steel autoclave, and the diaphragm dried in step (3) is placed vertically into the composite agent so that the composite agent covers the diaphragm, and then placed in a vacuum constant temperature drying oven at 120° C. and heated at a constant temperature for 24 h to obtain a composite NH2-UIO66 diaphragm.
[0068] (6) After the NH2-UIO66 composite membrane was taken out, it was washed several times with DMF and anhydrous ethanol respectively to remove the guest molecules, and then dried in a vacuum oven at 90°C for 12 h to obtain a polyphenylene sulfide fiber composite NH2-UIO66 membrane.
[0069] The surface resistance of the diaphragm of polyphenylene sulfide fiber composite NH2-UIO66 was tested by Princeton PARSTAT 3000-DX and was 0.36Ω.cm 2 According to the Chinese building materials industry standard JCT211-2009 Diaphragm Asbestos Cloth Standard, the air tightness of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm was tested to be 615 mm H2O. According to the method of Example 1, the weight of the diaphragm before and after the composite NH2-UIO66 was weighed using an electronic analytical balance, and the loading amount of NH2-UIO66 on the polyphenylene sulfide diaphragm was 10.41 mg / g.
[0070] Example 4
[0071] A method for preparing a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm:
[0072] (1) The polyphenylene sulfide fiber membrane was cut into a size of 3×3 cm and placed in deionized water for ultrasonic treatment for 5 min, and then placed in ethanol for ultrasonic treatment for 5 min. After repeating this process three times, the polyphenylene sulfide fiber membrane was placed in an oven and dried at 60°C for 12 h.
[0073] (2) The pretreated membrane was placed in a beaker containing 40 mL of 10 wt.% chlorosulfonic acid and heated in a water bath at 80°C for 1 h to obtain a sulfonated membrane.
[0074] (3) After the sulfonated membrane is taken out, it is washed with a large amount of deionized water until the deionized water after washing is neutral, and then placed in a vacuum oven and dried at 60°C.
[0075] (4) Preparation of composite agent: 0.135 g ZrO2 (1.1 mmol) and 0.099 g (0.55 mmol) diaminoterephthalic acid (the molar ratio of ZrO2 to NH2-BDC is 2:1) and 3 ml HCl solution were dissolved in 30 mL DMF and mixed by ultrasonication to obtain a composite agent with a pH of 1.3.
[0076] (5) The composite agent is loaded into a 50 mL polytetrafluoroethylene-lined steel autoclave, and the diaphragm dried in step (3) is placed vertically into the composite agent so that the composite agent covers the diaphragm, and then placed in a vacuum constant temperature drying oven at 120° C. and heated at a constant temperature for 24 h to obtain a composite NH2-UIO66 diaphragm.
[0077] (6) After the NH2-UIO66 composite membrane was taken out, it was washed several times with DMF and anhydrous ethanol respectively to remove the guest molecules, and then dried in a vacuum oven at 90°C for 12 h to obtain a polyphenylene sulfide fiber composite NH2-UIO66 membrane.
[0078] The surface resistance of the diaphragm of polyphenylene sulfide fiber composite NH2-UIO66 was tested by Princeton PARSTAT 3000-DX and was 0.38Ω.cm 2 According to the Chinese building materials industry standard JCT211-2009 Diaphragm Asbestos Cloth Standard, the air tightness of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm is 600 mm H2O. According to the method of Example 1, the weight of the diaphragm before and after the composite NH2-UIO66 is weighed using an electronic analytical balance, and the loading amount of NH2-UIO66 on the polyphenylene sulfide diaphragm is 10.11 mg / g.
[0079] Comparative Example 1
[0080] The experiment was conducted by changing the MOF material, namely replacing NH2-UIO66 with UIO66.
[0081] (1) The polyphenylene sulfide fiber membrane was cut into a size of 3×3 cm and placed in deionized water for ultrasonic treatment for 5 min, and then placed in ethanol for ultrasonic treatment for 5 min. After repeating this process three times, the polyphenylene sulfide fiber membrane was placed in an oven and dried at 60°C for 12 h to obtain a pretreated membrane.
[0082] (2) The pretreated membrane was placed in a beaker containing 40 mL of 98 wt.% concentrated sulfuric acid and heated in a water bath at 60°C for 1 h to obtain a sulfonated membrane.
[0083] (3) After the sulfonated membrane is taken out, it is washed with a large amount of deionized water until the deionized water after washing is neutral, and then placed in a vacuum oven and dried at 60°C.
[0084] (4) Preparation of the composite agent: 0.075 g of ZrCl4, 0.053 g of terephthalic acid (BDC) and 4.8 mL of acetic acid were dissolved in 40 mL of DMF solution and mixed by ultrasonication to obtain a composite agent with a pH of 1.89.
[0085] (5) The composite agent is loaded into a 50 mL polytetrafluoroethylene-lined steel autoclave, and the diaphragm dried in step (3) is placed vertically into the composite agent so that the composite agent covers the diaphragm, and then placed in a vacuum constant temperature drying oven at 120° C. and heated at a constant temperature for 48 h to obtain a composite UIO66 diaphragm.
[0086] (6) After the UIO66 composite membrane was taken out, it was washed several times with DMF and anhydrous ethanol respectively to remove the guest molecules, and then dried in a vacuum oven at 90°C for 12 h to obtain a polyphenylene sulfide fiber composite UIO66 membrane.
[0087] The water contact angle effect diagram of the polyphenylene sulfide fiber composite UIO66 diaphragm prepared in this comparative example is shown in Figure 6 .
[0088] The water contact angle of the polyphenylene sulfide fiber composite UIO66 diaphragm prepared in this comparative example is 86° ( Figure 6 ), the surface resistance is 1.14Ω.cm 2 , the air tightness is 527mm H2O. The test results show that although the composite UIO66 on polyphenylene sulfide fiber can achieve the purpose of reducing surface resistance and improving hydrophilicity and gas barrier properties, the performance of the diaphragm is far inferior to that of the composite NH2-UIO66 on polyphenylene sulfide fiber.
[0089] Comparative Example 2
[0090] Change the preparation method: replace chemical cross-linking with a physical coating method to coat NH2-UIO66 on the surface of the polyphenylene sulfide diaphragm through a binder.
[0091] (1) The polyphenylene sulfide fiber membrane was cut into a size of 3×3 cm and placed in deionized water for ultrasonic treatment for 5 min, and then placed in ethanol for ultrasonic treatment for 5 min. After repeating this process three times, the polyphenylene sulfide fiber membrane was placed in an oven and dried at 60°C for 12 h to obtain a pretreated membrane.
[0092] (2) The pretreated membrane was placed in a beaker containing 40 mL of 98 wt.% concentrated sulfuric acid and heated in a water bath at 60°C for 1 h to obtain a sulfonated membrane.
[0093] (3) After the sulfonated membrane is taken out, it is washed with a large amount of deionized water until the deionized water after washing is neutral, and then placed in a vacuum oven and dried at 60°C.
[0094] (4) Preparation of composite agent: 0.212 g (0.9 mmol) ZrCl4, 0.165 g (0.9 mmol) diaminoterephthalic acid (the molar ratio of ZrF4 and NH2-BDC is 1:1) and 0.078 mL HF were dissolved in 50 mL DMF and mixed by ultrasonic to obtain a composite agent with a pH of 1.85.
[0095] (5) The composite was placed in a 100 mL polytetrafluoroethylene-lined steel autoclave, and then placed in a vacuum constant temperature drying oven at 120°C and heated for 48 h. The resulting light yellow NH2-UIO66 powder was collected by centrifugation.
[0096] (6) Dissolve 1.42 g of polyvinylidene fluoride (PVDF) in 15 mL of DMF as a binder; then add 0.142 g of pore-forming agent polyvinylpyrrolidone (PVP); after the above materials are stirred evenly, add 0.142 g of NH2-UIO66 powder into the solution and stir again to obtain a yellow coating liquid. Take 10 mL of the coating liquid and evenly apply it on a 3×3 cm sulfonated polyphenylene sulfide membrane, so that the NH2-UIO66 coating loading is about 14.2 mg / g.
[0097] The water contact angle effect diagram of the polyphenylene sulfide fiber composite UIO66 diaphragm prepared in this comparative example is shown in Figure 7 .
[0098] After characterization, the contact angle of the composite membrane obtained by physical coating is 68°( Figure 7 ), the surface resistance is 1.53Ω.cm 2 , the air tightness is 615mm H2O. The test results show that the composite diaphragm prepared by physical coating method will lead to increased surface resistance, while the performance of the composite diaphragm prepared by chemical cross-linking method will be better.
[0099] Comparative Example 3
[0100] Zheng Hui used the coprecipitation method to synthesize ZIF-8 nanocrystals in "Preparation and Performance Research of Functionalized Super-hydrophobic Polyphenylene Sulfide Anti-corrosion Coating" (Zheng Hui. Preparation and Performance Research of Functionalized Super-hydrophobic Polyphenylene Sulfide Anti-corrosion Coating [D]. Northwest Normal University, 2023. DOI: 10.27410 / d.cnki.gxbfu.2023.000198.), and then grew silica balls on them. The obtained composite filler was mixed with PTFE and PPS for spraying, and then fired at high temperature to form a coating. The surface of the prepared composite coating is super-hydrophobic, and its hydrophobic angle reaches 135°.
[0101] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a polyphenylene sulfide fiber composite NH2-UIO66 diaphragm for alkaline water electrolysis, characterized in that: The method comprises the following steps: placing the polyphenylene sulfide fiber membrane in deionized water for ultrasonic treatment for 5 minutes, placing it in ethanol for ultrasonic treatment for 5 minutes, repeating the process for 3 times, placing the polyphenylene sulfide fiber membrane in an oven, and drying it at 60° C. for 12 hours to obtain a pretreated membrane; The pretreated polyphenylene sulfide fiber membrane is subjected to sulfonation treatment; a composite solution prepared by preparing NH2-UIO66 is added to the polyphenylene sulfide fiber membrane after sulfonation treatment, and a hydrothermal reaction is performed to obtain the polyphenylene sulfide fiber composite NH2-UIO66 membrane; The sulfonation treatment specifically includes: adding the pretreated polyphenylene sulfide fiber membrane to a sulfonation reagent, heating the reaction, and obtaining the sulfonated polyphenylene sulfide fiber membrane; The sulfonating agent includes concentrated sulfuric acid with a concentration of 50 to 98 wt.% or chlorosulfonic acid with a concentration of 5 to 20 wt.%; The temperature of the heating reaction is 60-80° C. and the time is 1-1.5 hours.
2. The preparation method according to claim 1, characterized in that: The components of the composite solution for preparing NH2-UIO66 include a zirconium source, an organic ligand, a solvent and an acid; the molar ratio of the zirconium source to the organic ligand is (1-3): (1-2); The zirconium source includes ZrF4, ZrCl4 or ZrO2.
3. The preparation method according to claim 2, characterized in that: The organic ligand includes diaminoterephthalic acid; the solvent includes N,N-dimethylformamide; and the acid includes acetic acid, hydrochloric acid or hydrofluoric acid.
4. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 100-150° C. and the time is 24-48 hours.
5. A diaphragm of polyphenylene sulfide fiber composite NH2-UIO66 prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the polyphenylene sulfide fiber composite NH2-UIO66 diaphragm according to claim 5 in hydrogen production by water electrolysis.
Citation Information
Patent Citations
Sulfonated polyphenylene sulfide proton exchange membrane and preparation method thereof
CN115084611A
Hydrogen production diaphragm as well as preparation method and application thereof
CN115896864A
Composite diaphragm for hydrogen production from alkaline electrolyzed water and capable of enhancing gas barrier property and preparation method of composite diaphragm
CN117107297A
Preparation method of polyphenylene sulfide alkaline electrolyzed water diaphragm
CN117328264A